THE POTENTIAL EFFECT OF L-CARNITINE AND EXERCISE ON MUSCLE STRENGTH IN AGING: A LITERATURE REVIEW - Kusuma Sri Whisnu Puteri; Kristina Puspadewi; Indira Vidiari Juhanna; I Putu Adiartha Griadhi (Sport and Fitness Journal, 2023)
Aging is an inevitable process, and it can affect various aspects of the human body, including the musculoskeletal system. L-carnitine (LC) has the potential to be used in conjunction with exercise to mitigate the loss of muscle strength associated with aging. This review aims to investigate the impact of LC and exercise on muscle strength in the context of aging. We conducted a comprehensive literature search using various online databases such as PubMed, EMBASE, CENTRAL, and Google Scholar. Our search involved keywords such as "L-carnitine," "exercise," "muscle strength," and "aging" to identify relevant literature. A total of 8 studies were included in this review and 7 of them were conducted in elderly. We present a narrative review to examine the role of exercise and L-carnitine in relation to muscle strength during the aging process. The combination of LC and exercise holds promise as a potential intervention. Both LC and exercise have shown benefits in mitigating the loss of muscle mass, strength, and function. However, when used together, they may yield even better results, particularly because LC can help improve functions that are typically impaired by aging. The decline in muscle mass, function, and subsequently strength associated with aging can significantly impact one's quality of life. LC and exercise both have impact to improve muscle strength in aging but further studies have to be made to assess precisely how the combination of both may benefit for the elderly. Keywords: aging; exercise; L-carnitine; muscle strength